The Relationship between Work Discipline and Motivation on Employee Performance at PT. Remaja Rosdakarya - Dewi Oktari, Sari; R. , Susanto; R. , Achmad Drajat Aji Sujai (International Journal of Psychosocial Rehabilitation, 2020)
Based on the results of interviews with the HR Manager at PT. Remaja Rosdakarya, employee performance from 2017 to 2018 has decreased. The purpose of this study was to determine the effect of work discipline and motivation, to find out how much the role of work discipline and motivation played, and to find out how much influence the work discipline and motivation had on employee performance at PT. Remaja Rosdakarya. The research method used is a descriptive and verificative method with a quantitative approach. The population in this study were employees of PT. Remaja Rosdakarya, with the same number of samples as the total population of 59 employees. The results showed that work discipline and motivation had a partial effect on employee performance at PT. Remaja Rosdakarya.